Hospital infection control and occupational medicine services in the face of the COVID-19 pandemic in occupational health - Silva Vieira, Angela Aparecida; de Carvalho, Suelaine Antônia; de Souza Floriano, Angela; Miranda de Oliveira Castro, Gabriela; Soares , Aleida Nazareth; de Melo Freire Júnior , Adelino; Damasceno de Souza, Amanda (Revista do Instituto Adolfo Lutz, 2022)
In this article, the actions developed by the Hospital Infection Control Service (HICS) and Occupational Medicine (OM) to face the COVID-19 pandemic and track cases of infection among employees of a large hospital in Belo Horizonte, Minas Gerais, Brazil. Training actions, guidelines on how to collect a swab sample, Code 19 (COVID-19) simulation, dressing/undressing, hand hygiene, the definition of flows, and the quantification of cases infected by COVID-19 among employees in care areas were highlighted. The engagement of HICS and OM in the prevention and promotion of health were fundamental to facing the pandemic. It is estimated that SARS-CoV-2 infection rates among staff at the study hospital were similar to those at other hospitals. The experience report is important for expanding knowledge about action planning in the context of a large hospital.